2014
DOI: 10.1099/vir.0.061648-0
|View full text |Cite
|
Sign up to set email alerts
|

Deletions in the highly polymorphic region (HPR) of infectious salmon anaemia virus HPR0 haemagglutinin–esterase enhance viral fusion and influence the interaction with the fusion protein

Abstract: Since the discovery of a non-virulent infectious salmon anaemia virus (ISAV) HPR0 variant, many studies have speculated on the functional role of deletions within the highly polymorphic region (HPR) of genomic segment 6, which codes for the haemagglutinin-esterase (HE) protein. To address this issue, mutant HE proteins with deletions in their HPR were generated from the Scottish HPR0 template (NWM10) and fusion-inducing activity was measured using lipid (octadecyl rhodamine B) and content mixing assays (firefl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…This is in agreement with our previous findings that non-virulent ISAV-HPR0 causes only a localized epithelial infection of mucosal surfaces of the gills and skin [19,49], whereas virulent ISAV-HPR-deleted shows a generalized endothelial infection of the circulatory system [50]. Furthermore, recent functional analysis demonstrated that deletions in the HE-HPR promote ISAV receptor fusion of viral and cellular membranes by which the virus delivers its genetic material into the host cell for subsequent replication [23]. Deletion of HPR facilitates the activation of the F protein post-receptor binding and subsequent proteolytic activation by a host cellular protease, while F protein mutations (including the Q 266 L substitution) directly influence proteolytic cleavage [24].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is in agreement with our previous findings that non-virulent ISAV-HPR0 causes only a localized epithelial infection of mucosal surfaces of the gills and skin [19,49], whereas virulent ISAV-HPR-deleted shows a generalized endothelial infection of the circulatory system [50]. Furthermore, recent functional analysis demonstrated that deletions in the HE-HPR promote ISAV receptor fusion of viral and cellular membranes by which the virus delivers its genetic material into the host cell for subsequent replication [23]. Deletion of HPR facilitates the activation of the F protein post-receptor binding and subsequent proteolytic activation by a host cellular protease, while F protein mutations (including the Q 266 L substitution) directly influence proteolytic cleavage [24].…”
Section: Discussionsupporting
confidence: 81%
“…All currently described pathogenic ISAV isolates associated with ISA disease have deletions in the HPR with over 30 different HPR-deleted subtypes identified in Europe, North America and Chile [16][17][18][19][20][21][22]. Sequencing and functional characterization further suggest both HPR-deletion and a Q 266 L substitution, or insertion adjacent to the cleavage site in the F protein influences ISAV virulence [22], by promoting viral fusion and the activation of proteolytic cleavage [23,24]. However, other viral functions, for example virus receptor binding [25], virus uptake, replication rate, shedding of new virions [26,27], modulation of the host immune response [28,29] and the ability to spread to new hosts [30], can also influence virulence.…”
Section: Introductionmentioning
confidence: 99%
“…During cell surface adhesion and activation of the fusion mechanism, the ISAV HE and F proteins become physically separated from each other on the viral surface. This is a key step for viral entry into the cell (41). In relation to the presently observed positive effect, it is reasonable to hypothesize that a peptide interacting with either HE or F prior to viral adhesion and cell infection might affect the dynamics between these two proteins, enhancing protein dissociation and selectively modifying the fusion and viral entry processes.…”
Section: Discussionmentioning
confidence: 99%
“…Initial attachment of ISAV to terminal 4-O-acetylsialic acid (4-OAS) glycans on host cells is mediated through HE, whereas F mediates virus-host fusion. The ISAV HE and F glycoproteins colocalize on virions and form a heteromeric preentry complex of unknown stoichiometry (3). Binding of erythrocyte ghosts to cells expressing the ISAV preentry complex induces dissociation of ISAV F from HE, presumably acting as a trigger for membrane fusion.…”
mentioning
confidence: 99%
“…Binding of erythrocyte ghosts to cells expressing the ISAV preentry complex induces dissociation of ISAV F from HE, presumably acting as a trigger for membrane fusion. Interestingly, HE proteins from low-virulence strains of ISAV show a higher affinity to the F protein on erythrocyte ghost binding and correlate with a lower fusion activity and a longer highly polymorphic region (HPR) (3).…”
mentioning
confidence: 99%